ANALISIS KUALITAS PELAYANAN DAN HARGA PRODUK YANG BERPENGARUH TERHADAP KEPUASAN UNTUK MENGURANGI PERPINDAHAN MEREK PENGGUNA XL AXIATA PADA MAHASISWA UNIVERSITAS DIPONEGORO - Pransisya, Megie; Sudaryanto, Budi (Diponegoro Journal of Management, 2017)
The development of communication technology, especially mobile phones makes the competition of cellular service providers (mobile operators) becomes increasingly competitive. This condition makes the service users have many options and sometimes they decide to switch their brand to the other operators because of some reasons. XL Axiata, is one of the most popular cellular operators in Indonesia that had experienced the impact of brand switching. XL Axiata lost the number of its users from 59.6 million users in 2014 to 42.1 million users in 2015. The phenomenon of brand switching then shifts XL Axiata’s position to the fourth place. This achievement is worse than the previous one when they reached to the second position and become one of the most dominant market controls.This study uses four variables; quality of service, price, satisfaction, and brand switching. Testing the hypothesis in this study is supported by the data in which there were 107 respondents using analytical techniques Structural Equation Modeling (SEM) through AMOS 22.This study produces 5 processes to reduce brand switching performed by XL Axiata users. However, the most influential process to the reduce brand switching is to improve the quality of service in order to increase the satisfaction of the customers. Increasing satisfaction will further reduce the phenomenon of brand switching by XL Axiata users.